Babayaga Krepek Brownies / Ali Imran Mohaini - Mohaini, Ali Imran (2021)
Babayaga Krepek brownies offer brownie-based food products that are made into chips to provide customer satisfaction. This identifies people who want to eat cracker brownies as their snack. It is an affordable product price. It also targets children, families, and students to buy this product. Babayaga Krepek's marketing strategy is product selection and pricing. It offers a reasonable price because many people want to buy this special product in Melaka and Malaysia. So I developed a marketing strategy that paid attention to buying Babayaga Krepek Brownies. It tastes good and the product is high quality. Ali Imran Bin Mohaini is in charge of Babayaga Krepek Brownies. I created a Facebook page to promote my business through social media, and I learned how to make a Facebook post for a business product, whether it is a teaser post, a soft sale, or a hard sell. To minimize profit drops, I must also increase sales and spend prudently on my goods. I need to market the product through social media throughout Malaysia, particularly in Malacca. I'm also learning how to utilize eCommerce to track sales. Selling this product as my endeavor is a challenge for me.